Islamic Ethics: Concept and Prospect (American Journal of Islam and Society, 1989)
The paper is incomplete in its present form. Its discussion about Islamic Ethicsis superficial. Neither the complexity of theological ethics nor are philosophicaland juridical ethics admitted anywhere. Moreover, it does not evaluate thepresent status of works on ethics (e.g., Isma'il al Faruqi's contribution) andthe scholarship produced by academics like Hourani (The Ethics of 'Abd Al-Jabbar).The paper must be expanded with proper discussion about the conceptualdifficulties and the Islamic alternative. Certainly there is a need forthis discussion, but not so superficially ...